Influence of competitive activity on the development of self-realization among adolescents - Ekaterina Mikhailovna Akishina; Elena Petrovna Olesina; Alexey Igorevich Mazanov (Institute of Advanced Engineering and Science, 2022)
The article examines the problems of social self-realization of modern adolescents in competitive activity. Based on the conducted scientific studies, the authors determine the important role of competitions in the process of school students’ socialization. The article presents the most important criteria of adolescents’ level of self-realization in competition activity such as self-esteem adequacy, creativity, self-organization, teamwork, and stress resistance, as well as the results of studying the level of development of such paired personality traits as sociability/insularity and friendliness/aggressiveness developing in adolescents in competitive activities. The authors emphasize the high degree of risk of any contests as the participants experience worry, fear, and stress. The article presents a comparative analysis of studies of the level of socialization in school students conducted in the years 1999, 2013, 2019, and 2020. Authors prove that competition is a relevant form of developing social personality traits in school students in modern society. It is necessary to create certain pedagogical conditions when preparing and holding a competition and ensure pedagogical assistance and support to minimize the possible risks. It is important for modern pedagogics to study and account for childhood and adolescent fear, as well as psychological and pedagogical risks of carrying out competitions for school students.